Exploring The Employee Perspective of Competency development Practices in the Public Sector: A Case Study of the Indonesian Food and Drug Authority (BPOM) - Panggabean, Lamtioma Franita; Pertiwi, Kanti (Magister Ilmu Administrasi Publik, 2024)
Following the end of the New Order regime and reform initiatives promoted by the World Bank, the Indonesian government increasingly adopted New Public Management (NPM). With NPM, the skills and competencies of the State Civil Apparatus, as agents of bureaucratic reform, must be enhanced to meet organizational goals. However, these goals often conflict with employees' interests. Therefore, it is crucial to consider employees' perspectives when developing competencies. This research examines employees' views on competency development and the role of leaders. Using qualitative methods, 12 public sector employees were interviewed through an exploratory survey. The findings indicate that competency development is often linked to financial well-being, while other interpretations are overshadowed by different priorities. The practical implication is that the government should tailor its human resource policies and practices to achieve desired outcomes.